Representações sociais de pacientes renais crônicos sobre a hipotensão arterial - Oliveira, Fernanda Celedonio de (2009)
The chronic renal disease is considered a progressive pathology and an important public health problem. In Brazil, the number of patients undergoing any of the different dialysis modalities keeps growing. During the dialysis sessions, countless complications may occur, such as arterial hypotension, which occurs in 25% of the sessions. This study was aimed to screen the representation by gender within the chronic renal disease patient population with hypotension episodes during hemodialysis. The study was carried out between March and May 2009, using a descriptive, exploratory, quantitative and qualitative methodology based on the Social Representation Theory. The study was done at a hemodialysis clinic in the City of Fortaleza serving the state-run health service (SUS), over a population of 50 chronic renal patients suffering from arterial hypotension episodes during dialysis. Data were obtained from the patients´ clinical history by a multi-method approach, a free association of words with inducing stimuli, narrative interviews and collages. Data obtained from the clinical histories and from the free association of words were organized in Excel spreadsheets, while the qualitative data, i.e. the interview and collage, were organized by narrative lines (Spink) and the expression technique, respectively. All legal and ethics norms were followed pursuant to Resolution 196/96, which regulates the research on human beings. The results show a dominance of women, an age range of over 60 years, illiterate, married, catholic, retired, patients with a family income of about one minimum wage, residents of the capital city, mainly with HAS and DM as the cause for dialysis. They evoked 200 words, chosen regarding the central core and periphery. 30 patients were interviewed and were classified in 7 categories. Finally, 45 patients used the collage and were classified into 13 categories. We noticed that the social representations are more pessimistic and negative in men. They associated AH to sweating, fear, bad sight and death, and reported that after the initiation of treatment the limitations imposed by the illness made their daily life more difficult. They also reported changes in previously developed activities and associated the illness limitations to a lack of freedom, prison and fire. The social representations of women were expressed in a more cautious and sentimental way. They associated AH to sweating, fear, bad sight and pain. They reported positive attitudes, dealt well with the condition, and mentioned religious aspects and future plans as tools to face and overcome the illness. Shared images related to the difficulties related to the new dietary habits were common, yet highlighting their ability to come to terms with it. We concluded that many things can be done for chronic renal patients as well as for the professionals taking care of them. By knowing the particularities of each individual, it would be possible to apply healthcare promotion principles aimed to improve the patients´ quality of life.